Race neutrality : rationalizing remedies to racial inequality - Myers, Samuel L.; Ha, Inhyuck (Lexington Books, 2018)
"Using illustrations from research on racial inequality in varied domains from public procurement and contracting to mortgage lending to child maltreatment to competitive swimming, Race Neutrality: Rationalizing Remedies to Racial Inequality argues that race neutrality--while desirable on its face--often fails to do what it is intended to do"--